The European union and occupied Palestinian territories : state-building without a state - Bouris, Dimitris <<[VerfasserIn]>> (Routledge, Taylor & Francis Group, 2014)
"This book evaluates the present European Union (EU) approach to state-building, both in policy and operation. It offers a review of the literature on (EU) peace building, EU, state-building and conflict resolution, before examining in detail the European Union's role as a state-builder in the case of the Occupied Palestinian Territories following the 1993 Oslo Accords.Drawing on extensive fieldwork and over 140 interviews carried out in Brussels, London, Jerusalem and Ramallah with EU, Palestinian and Israeli officials as well as academics, members of NGOs and civil society, the author evaluates the present approach of state-building and offers a framework to test the effectiveness of the EU as a state-builder. Examining security sector reform, judiciary sector reform and the rule of law, the book measures the contribution of the EU to state-building against a backdrop of on-going conflict and a polarised social setting.This book will be of interest to students and scholars of international relations, EU politics, Middle Eastern politics and state-building"–
Includes bibliographical references (pages 176-205) and index